Enriching Students' Vocabulary Using English Pop Songs - Limbong, Roimma (JET (Journal of English Teaching), 2012)
This study aimed at enriching kindergarten students' English vocabulary at Singa School, Jakarta. The participants were 21 students of the K-2 grade. The action research was conducted in two cycles, in which the participants were taught vocabulary by using pop-songs. The quantitative data, collected using tests, and the qualitative data, collected using observation and document study techniques indicated that the use of pop-songs enriched the participants' vocabulary, as shown by the increase of the mean scores of the tests conducted, i.e. 33.57 (in the pre-test) to 50 ( post-test of Cycle I) to and 80 (post-test of Cycle II). The t-tests in the two cycles resulted in tcount (7.087)>ttable (1.725) and tcount (9.216) >ttable (1.725, respectively. Based on the findings, it could be concluded that the use of pop-songs was effective to enrich kindergarten students' vocabulary.